Membebaskan Makna Sesama dari Kekangan Ghetto: Menjadi Gereja yang Merangkul Sesama dari Perspektif Lukas 10:25-37 - Blegur, Romelus (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
The diversity of life and its complexity is a rich social fact and should be celebrated through encounters between fellow humans, but it is often harmed by forms of discrimination and self-limitation that narrow these relationships. This then restricts the existence of human life in narrow spaces like ghettos which isolate people from their social, cultural and religious contexts. This type of life is of course not permitted by the church, but often the church also participates in it. This is a historical burden that continues as previously seen in the text of Luke 10:25-37. The method used in this research is a library research method using library sources that are relevant to this research, as well as an interpretive or hermeneutic method to interpret the meaning of the biblical text for the current context. The results of this research are: first, the text of Luke 10:25-37 questions the meaning of fellow human beings, which the Israelites failed to practice compared to the Samaritans. In this text Jesus chooses to side with the actions of the Samaritans and criticizes the actions of the Israelites. Second, the text of Luke 10:25-37 reveals that the meaning of neighbor is universal and the church is required to side with Jesus' call to participate in building universal relationships with fellow humans beyond social, cultural and religious barriers. Third, the Church must free the meaning of others from the constraints of the ghetto that alienates their existence from the world.